Canada Goose Management Series: Harassment - Drake, David (Rutgers New Jersey Agricultural Experiment Station, Rutgers Cooperative Extension, 2004)
There is a wide range of non-lethal and lethal options available for Canada goose ( Branta canadensis ) management. This fact sheet, part of a series that examines goose management options currently employed, will present information on harassment techniques that may deter geese from visiting your property. Harassment techniques such as pyrotechnics, propane cannons, properly trained dogs, and visual deterrents can be effective in deterring Canada geese from entering a particular area. We define the techniques and explore the advantages and disadvantages of harassment in terms of, among other factors, amount of effort required to implement, effectiveness, and cost. Fact Sheet FS1032 Purpose: To provide information about managing Canadian geese by harassment